Techno - socio economic analysis of house terrace cultivation in Thiruvananthapuram corporation - Greeshma Udayan (Department of Agricultural Extension, College of Agriculture, 2017)
The present study entitled “Techno socio economic analysis of house terrace cultivation in Thiruvananthapuram Corporation” was carried out to study the extent of awareness and adoption on house terrace cultivation as recommended in adhoc package of practices for organic farming, health consciousness, inventorisation of agencies promoting house terrace cultivation and documentation of practices followed by the respondents. The study was conducted in six wards of Thiruvananthapuram Corporation namely Poojappura, Nemom, Kudappanakunnu, Kazhakuttom, Vizhinjam and Kadakampally. One hundred and twenty members of urban households involved in house terrace cultivation were selected by random sampling from six selected wards. A well-structured interview schedule was used for data collection from the respondents. Four dependent variables and nine independent variables were selected and analyzed with the help of different statistical tools like mean, quartile deviation, frequency, percentage and correlation. It was found that majority (56.67%) of the respondents belonged to the middle age having degree (65.83%) with an annual income more than 4 lakhs (39.17%). The analysis of the profile characteristics indicates that most of respondents belonged to medium category of innovation proneness (52.50%), family labour utilization (55.83%), risk orientation (50.83%), economic motivation (55%) and extension agency contact (52.50%). Most of the urban households had high knowledge (79.17%) on house terrace cultivation. Majority (48.33%) of the respondents belonged to medium level of awareness on house terrace cultivation and had positive and significant correlation with the variables like educational status, innovation proneness, family labour utilization, risk orientation, economic motivation and extension agency contact Regarding the extent of adoption, 54.17% of respondents belonged to medium category and had positive and significant correlation with all the profile characteristics. Majority (40.83%) of the respondents belonged to early majority adoption category followed by early adopters (25.83%), late majority (21.67%) and laggards (10.83%). More than half of the respondents (60.83%) belonged to medium level of health consciousness. It had positive and significant relationship with variables like age, annual income, educational status, knowledge on house terrace cultivation, risk orientation, economic motivation and extension agency contact. It was found that majority of the respondents (57.50%) comes under the benefit cost ratio of 1.40 to 2.37 and it had positive and significant relationship with annual income, educational status, innovation proneness, risk orientation, economic motivation and extension agency contact. The study revealed that the major agencies promoting house terrace cultivation were Krishi bhavan, Kerala Irrigation Infrastructure Development Corporation, Integrated Farming System Research Station, Karamana, State Horticultural Mission and Department of Environment and climate change.